Transformación estable en variedad comercial del programa de mejoramiento de arroz de INTA - Faccio, Paula Daniela; Ameijeiras, Sara; Beznec, Ailin; Colazo, Jose; Bossio, Adrian Ezequiel (REDBIO, 2025)
Póster